2016
DOI: 10.1098/rspb.2015.2652
|View full text |Cite
|
Sign up to set email alerts
|

Touch sensation by pectoral fins of the catfishPimelodus pictus

Abstract: Mechanosensation is fundamental to many tetrapod limb functions, yet it remains largely uninvestigated in the paired fins of fishes, limb homologues. Here we examine whether membranous fins may function as passive structures for touch sensation. We investigate the pectoral fins of the pictus catfish (Pimelodus pictus), a species that lives in close association with the benthic substrate and whose fins are positioned near its ventral margin. Kinematic analysis shows that the pectoral fins are held partially pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In combination with previous work in the pectoral fin [18,19], the discovery that adipose fins, which are passive median fins, can function as mechanosensors suggests that mechanosensation might be a general feature of fins. These results broaden our understanding of adipose fin function and also inform the evolution of proprioception in vertebrate appendages.…”
Section: Discussionmentioning
confidence: 98%
“…In combination with previous work in the pectoral fin [18,19], the discovery that adipose fins, which are passive median fins, can function as mechanosensors suggests that mechanosensation might be a general feature of fins. These results broaden our understanding of adipose fin function and also inform the evolution of proprioception in vertebrate appendages.…”
Section: Discussionmentioning
confidence: 98%
“…Heterobranchus longifilis : Kerdchuen & Legendre, ; Clarias gariepinus : Britz & Pienaar, ; Silurus glanis : Kozlowski & Poczyczynski, ; Mystus nemurus : Rahmah et al, ; Lophiosilurus alexandri : Kitagawa et al, ; Hatcheria macraei : Barriga, Espinos, Walter, & Miguel, ). Moreover, their elongated body shape along with flattened head having subterminal mouth and a prognathic upper lip, barbels and very small dorsal eyes enable them like other catfishes to use tactile techniques rather than visual sense for feeding (Alexander, ; Hardy, Steinworth, & Hale, ). Thus, these unique characteristics make them perfect nocturnal feeders and locomotors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the fins of the bluegill sunfish Lepomis macrochirus Rafinesque 1819 have shown that bending of the fin rays stimulates a mechanosensory response that allows it to avoid obstacles (Flammang & Lauder, ; Williams et al , ). Furthermore, the membranous pectoral fins of the pictus catfish Pimelodus pictus Steindachner 1876 have been shown to be passive mechanosensors, responding to both touch and bend stimulation (Hardy et al , ). The adipose fin of salmonids does not possess fin rays but it does have a system of overlapping actinotrichia.…”
Section: Discussionmentioning
confidence: 99%